LC-MS analysis, antioxidant and anti-inflamatory activity, isolation of secondary metabolite of ethanol extract stem of Etlingera rubroloba AD Poulsen - Asriullah Jabbar; Muhammad Ilyas Y; Wahyuni; Hasyrul Hamzah; Anjar Windarsih; Sylvia Utami Tunjung Pratiwi; Abdul Rohman (Case Studies in Chemical and Environmental Engineering)
This research was performed to evaluate the antioxidant and anti-inflammatory activities of ethanolic extract of Etlingera rubroloba AD stems and its metabolites. The IC50 values of antioxidant activity test of using ABTS and CUPRAC methods were 16.27 ± 0.23 μg/mL and 12.10 ± 0.32 μg/mL, respectively. The anti-inflammatory test (Interleukin 1β) of the ethanolic extract doses of 200, 300 and 400 mg/kg BW showed activities at concentration of 68.2, 32.42 and 25.31 ρg/mL, whereas Interleukin 12 activity test gave activity at concentrations of 869.99, 708.74 and 369.58 ρg/mL, respectively. The compound sinapyl alcohol acetate was firstly reported in ethanolic extract of E. rubroloba stem.